Ernst Krenek and the politics of musical style - Tregear, Peter (The Scarecrow Press, 2013)
Focusing on Krenek's compositional path from the eclectic musical language of Jonny spielt auf to the austere twelve-tone technique of Karl V. Tregear provides an historical and critical context to this most historically significant period of Krenek's creative life. His study also enriches our understanding of many of Krenek's contemporaries, such as Alban Berg and Arnold Schoenberg. This book should interest students, scholars and practitioners with an interest in modern o
Keywords: Krenek, Ernst, : 1900-1991 : Songs and music : History and criticism; Opera : Germany : 20th century